1992
DOI: 10.1111/j.1432-1033.1992.tb17126.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characterisation of recombinant human haemoglobin A expressed in Saccharomyces cerevisiae

Abstract: Recombinant human HbA, produced by co-expressing a-globin and P-globin chains in the yeast Saccharomyces cerevisiae, has been characterised extensively both physically and functionally. Structural studies using N-terminal sequence analysis, peptide mapping, amino acid composition analysis and electrospray MS demonstrated that the recombinant protein was identical to standard HbA purified from erythrocytes. The functional properties of the recombinant protein were assessed using equilibrium and kinetic measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
(6 reference statements)
0
16
0
Order By: Relevance
“…To see this illustration in color, the reader is referred to the web version of this article at www.liebertpub.com/ars in the erythrocytes (135). Expression of rHb in E. coli and S. cerevisiae was also accomplished with impressive yields (i.e., 2%-10% of the total cellular protein content consists of Hb) (2,28,52,62,74,79,96,97,136,156). Although each system has its own set of advantages and drawbacks, most recent efforts have focused on E. coli production systems.…”
Section: Historical Overview Of Recombinant Hbmentioning
confidence: 99%
“…To see this illustration in color, the reader is referred to the web version of this article at www.liebertpub.com/ars in the erythrocytes (135). Expression of rHb in E. coli and S. cerevisiae was also accomplished with impressive yields (i.e., 2%-10% of the total cellular protein content consists of Hb) (2,28,52,62,74,79,96,97,136,156). Although each system has its own set of advantages and drawbacks, most recent efforts have focused on E. coli production systems.…”
Section: Historical Overview Of Recombinant Hbmentioning
confidence: 99%
“…Our previous report has shown that the ␤ chain can also be expressed from cDNA clones as insoluble aggregates using a T7 promoter without the use of a fusion protein, thus circumventing some of the laborious problems associated with a fusion protein expression system (9). Unlike yeast (16,17) and the fusion protein expression systems, this construction leaves the initiator methionine on the N terminus. Characterization of three N-terminal ␤ chain mutants produced in E. coli using the T7 expression system (␤1 ϩ Met,…”
mentioning
confidence: 99%
“…There are several systems currently available for producing normal or sickle recombinant Hb (Nagai et al, 1985;Baudin-Chich et al, 1990;Wagenbach et al, 1991;Adachi et al, 1992Bihoreau et al, 1992Coghlan et al, 1992;Looker et al, 1992;Martin de Llano et al, 1993a, 1993bShen et al, 1993;Vallone et al, 1993). Previous reports have shown that the recombinant sickle Hb produced in yeast closely resembles natural Hb, i.e., , 1993a, 1993b).…”
Section: Discussionmentioning
confidence: 99%